Peran Akuntansi Manajemen Dalam Pengendalian Biaya Operasional Untuk Meningkatkan Kinerja Keuangan Pada Koperasi Simpan Pinjam Credit Union Bahtera Sejahtera Maumere - Fridaputri, Katharina; Niken Aurelia, Pipiet; De Romario, Fransiscus (Jurnal Projemen UNIPA, 2026)
This internship program aims to find out the important role of management accountability in controlling operational costs to improve financial performance in savings and loan cooperatives of Bahtera Sejahtera Credit Union.The research method used is a descriptive qualitative approach with data collection techniques through observation,interviews,and documentation. The role of management accounting in controlling operational costs to improve financial performance in the Bahtera Sejahtera Maumere Credit Union savings and loan cooperative,it can be concluded that management accounting has a very important role in supporting management decision-making.Through the application of management accounting,cooperatives can plan,control,and evaluate operational costs more effectively and efficiently. Controlling operational costs through budgeting,cost analysis,and internal financial reporting can help management identify cost wastage and improve resource use efficiency.This has a positive impact on the financial performance of cooperatives,which is reflected in increased operational effectiveness and financial stability. Thus,the implementation of good management accounting in the Bahtera Sejahtera Maumere Credit Union savings and loan cooperative can be a strategic tool in improving financial performance and supporting the sustainability and growth of the cooperative can be a strategic tool in improving financial performance and supporting the sustainability and growth of the cooperative in the future